2009
DOI: 10.1542/peds.2009-0041
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Adult Care for Youths With Diabetes Mellitus: Findings From a Universal Health Care System

Abstract: During the transition to adult health care, there is increased risk of DM-related hospitalizations, although this may be attenuated in youths for whom there is physician continuity. Eye care visits were not related to transition; however, rates were below evidence-based guideline recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
238
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(246 citation statements)
references
References 38 publications
3
238
1
4
Order By: Relevance
“…Joint transfer meetings may have the potential to provide in-depth information about AHC and to decrease the anxiety for adolescents and their parents about treatment of the chronic disease with an unknown adult specialist within the AHC system [4]. In addition, joint transfer meetings and other settings of transition programs such as an earlier integration of the adult specialist team into care (e.g., transition clinics) could potentially reduce levels of anxiety and improve continuity of care [4,17,21]. If geographical distance is an obstacle for joint meetings, other frameworks of support such as a health navigator system may be helpful in providing appropriate information to the adolescent patient during the transition process [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint transfer meetings may have the potential to provide in-depth information about AHC and to decrease the anxiety for adolescents and their parents about treatment of the chronic disease with an unknown adult specialist within the AHC system [4]. In addition, joint transfer meetings and other settings of transition programs such as an earlier integration of the adult specialist team into care (e.g., transition clinics) could potentially reduce levels of anxiety and improve continuity of care [4,17,21]. If geographical distance is an obstacle for joint meetings, other frameworks of support such as a health navigator system may be helpful in providing appropriate information to the adolescent patient during the transition process [29].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the concept of transition emerged, defined as a process of "a purposeful planned movement of adolescents and young adults with chronic physical and medical conditions from child-centered to adult-orientated health care systems" [3]. Unfortunately, the transfer to AHC is still often the result of an ad hoc decision, and some adolescents even drop out of the health care system temporarily until they seek help for acute medical problems in the AHC system [17,18,23,30,32]. Such poor transition processes may have significant negative effects on morbidity and mortality in young adults [2,10,17].…”
Section: Ahc Adult Health Carementioning
confidence: 99%
“…In general, when there is no formal transition program in place, a "loss to follow-up" rate of > 20-25% can be expected in the 2-4 years after discharge from the pediatric center. [6][7][8][9][10][11][12] One study from Finland showed a significant improvement in metabolic control after transition to adult care, although other studies have failed to confirm this. 6 Of note, in a recent health services study of 1,507 adolescents with diabetes undergoing a transition of care at 18 years of age in the Province of Ontario, Canada, we reported two important findings: there was a small but significant increased risk of hospitalization for Adolescents leaving their pediatric team and starting afresh with a new physician and new team were more likely to be hospitalized for DKA than those whose adult team included some of the members of their pediatric team.…”
Section: Studies Of Transition Outcomesmentioning
confidence: 99%
“…6 Of note, in a recent health services study of 1,507 adolescents with diabetes undergoing a transition of care at 18 years of age in the Province of Ontario, Canada, we reported two important findings: there was a small but significant increased risk of hospitalization for Adolescents leaving their pediatric team and starting afresh with a new physician and new team were more likely to be hospitalized for DKA than those whose adult team included some of the members of their pediatric team. 12 This suggests that some continuity of care should be a consideration during transition. Table 2 summarizes the major intervention studies.…”
Section: Studies Of Transition Outcomesmentioning
confidence: 99%
“…43 Studies in young adults with diabetes and renal transplant recipients using objective markers of non-adherence 49,50 confirm lower adherence to maintenance therapies in young adults compared with adults. Allowing for the small number of patients who were non-adherent in this study, there were no differences in the proportions of non-adherent or adherent, adult or adolescent patients' responses to the individual questions of the MMAS-8 (data not shown).…”
mentioning
confidence: 98%